A rare case of streptococcus gordonii peritonitis in a patient on peritoneal dialysis - Lim, Christopher Thiam Seong; Then, Ru Fah (Pakistan Medical Association Rawalpindi Islamabad Branch, 2017)
Peritonitis is a known complication among end stage renal disease patients undergoing peritoneal dialysis (PD). Gram positive species such as staphylococcus are commonly grown. However, cultures may yield rare organisms such as streptococcus gordonii; a subgroup of viridians streptococcous. Most causes of PD peritonitis come from touch contamination but streptococcus gordonii causing PD peritonitis is postulated to originate from the oral cavity. We report a rare case of streptococcus gordonii PD peritonitis in our tertiary renal hospital, in a patient with poor dental hygiene. This is the third reported case of streptococcus gordonii PD peritonitis in the literature. We have demonstrated that early identification of the organism and source can lead to successful treatment.